Method for preparing carbon-coated ruthenium fiber with large length-diameter ratio in short process

By electrolyzing inorganic ruthenium salt and carbon salt in molten salt, carbon coated ruthenium fibers are directly prepared, which solves the problems of complex existing process flow and serious waste emissions, and achieves a brief and environmentally friendly preparation process, which meets the requirements of low-carbon green circular economy.

CN119920632APending Publication Date: 2025-05-02NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510177142.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing carbonaceous fiber materials have complex process, high equipment requirements, and serious waste emissions, making it difficult to meet the development needs of low-carbon green circular economy.

Method used

The short-process process is adopted to convert the inorganic ruthenium salt and carbon salt directly into carbon-coated ruthenium fibers in molten salt through electrolysis. The electrolytic heating process is driven by green electricity to avoid the discharge of polluted waste gas and waste liquid.

Benefits of technology

The effective co-electrical reduction of ruthenium and carbon elements in raw materials was achieved, and carbon-coated ruthenium fibers were prepared directly and short-process electrolyzed. The process was short, the equipment requirements were low, and environmentally friendly and harmless waste emissions were met, which was in line with the strategic needs of green manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920632A_ABST
    Figure CN119920632A_ABST
Patent Text Reader

Abstract

The invention discloses a short-process method for preparing carbon-coated ruthenium fibers with a large length-diameter ratio, which comprises the following steps: 1, taking inorganic ruthenium salt and carbon-containing salt as a ruthenium source and a carbon source, uniformly mixing the ruthenium source and the carbon source with alkali metal or / and alkaline earth metal inorganic salt, and drying in a drying oven for not less than 12 hours to obtain a mixed salt material; 2, heating the mixed salt material in a crucible in an inert atmosphere in a vertical tubular resistance furnace to form stable liquid molten salt, and lowering two electrodes consisting of a non-carbon anode and a conductive cathode to be below the liquid level of the liquid molten salt for electrolysis; and 3, after electrolysis is completed, the non-carbon anode and the conductive cathode are lifted away from the liquid level of the liquid molten salt, a cathode product is stripped after the furnace temperature is reduced to the room temperature, and the carbon-coated ruthenium fiber with the large length-diameter ratio is obtained after repeated cleaning with deionized water and diluted hydrochloric acid. The method is driven by green electric energy, the process is simple and easy to operate, no obvious three-waste discharge exists, the method is environmentally friendly, and a good optional process path is provided for green short-process material preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of micro-nano materials, and in particular to the field of micro-nano material preparation technology, and specifically to a method for preparing carbon-coated ruthenium fibers with a large aspect ratio in a short process. Background Art

[0002] With the continuous development of society, green and sustainable energy utilization has attracted much attention from all parties, and higher requirements have been put forward for the energy supply of new energy equipment, special equipment and conventional equipment. The development of efficient energy storage devices is becoming increasingly urgent. As an emerging energy storage device, supercapacitors are gradually recognized for their green and environmentally friendly, long life and high power density. The key to good supercapacitor performance lies in excellent electrode materials. Carbonaceous materials are the focus of scientists from various countries in many electrode material studies.

[0003] Kierzek et al. activated carbon with high specific surface area by high temperature activation of coal and asphalt at 800 °C for 5 h with KOH, and obtained activated carbon with different porosities and high specific surface area as electrode materials for supercapacitors. -1 The specific capacity of activated carbon fiber-carbon nanotube self-supporting electrode was prepared by Liu et al., and its surface area can reach 825m 2 ·g -1 The specific capacitance obtained after being used as a supercapacitor electrode is 216F·g -1 (1.0 mol L -1 H2SO4 solution, current density 1.0A·g -1 ); In addition, Wu Zhongshuai disclosed a ruthenium / carbon nanotube flexible positive electrode material and its preparation method and application (CN113725444A) in 2020. It uses filter paper as a flexible porous matrix and combines carbon nanotube adsorption with ruthenium nanoparticle loading process to prepare ruthenium / carbon nanotubes. When used as a battery positive electrode material, it exhibits good charge and discharge performance. Numerous public data show that carbonaceous fiber materials have good application performance as emerging device energy storage materials. However, the current common preparation processes have complex processes and large amounts of wastewater and waste gas emissions, which have not yet been paid attention to. Therefore, it is of great value to develop a short-process, green and harmless preparation method. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing carbon-coated ruthenium fibers with a large aspect ratio in a short process in view of the deficiencies of the above-mentioned prior art. The method fully realizes the effective co-electroreduction of ruthenium and carbon elements in the raw materials, and can directly obtain carbon-coated ruthenium fibers by short-process electrolysis. The electrolysis and heating process can be driven by green electricity, and there is no pollution waste gas or waste liquid discharge, which solves the problems of complex material preparation process, high equipment requirements, and serious three waste discharge, and meets the current development needs of low-carbon green circular economy.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing carbon-coated ruthenium fibers with a large aspect ratio by a short process, characterized in that the method comprises the following steps:

[0006] Step 1: Mixing an inorganic ruthenium salt and a carbon-containing salt as a ruthenium source and a carbon source with an alkali metal or / and an alkaline earth metal inorganic salt, and then drying the mixture in a drying oven for not less than 12 hours to obtain a mixed salt material;

[0007] Step 2: heating the mixed salt material obtained in step 1 in a crucible in an inert atmosphere in a vertical tubular resistance furnace to form a stable liquid molten salt, and then lowering a two-electrode system consisting of a non-carbon anode and a conductive cathode below the liquid molten salt surface for electrolysis;

[0008] Step 3. After the electrolysis in step 2 is completed, the non-carbon anode and the conductive cathode are lifted off the surface of the liquid molten salt. After the furnace temperature drops to room temperature, the product on the conductive cathode is peeled off, and the large aspect ratio carbon-coated ruthenium fiber is directly obtained after repeated washing with deionized water and dilute hydrochloric acid.

[0009] The above-mentioned short-process method for preparing carbon-coated ruthenium fibers with a large aspect ratio is characterized in that the inorganic ruthenium salt in step one is one of RuCl3, RuCl3*nH2O, K2RuCl6, Na2RuCl5*nH2O, and RuO2; and the amount of inorganic ruthenium salt added is 1.0% to 5.0% of the mixed salt material in terms of mass fraction.

[0010] The above-mentioned short-process method for preparing large aspect ratio carbon-coated ruthenium fibers is characterized in that the carbon-containing salt in step one is one of Na2CO3, Li2CO3, K2CO3, CaCO3, MgCO3, and BaCO3; and the amount of carbon-containing salt added is 5% to 10% of the mixed salt material in terms of mass fraction.

[0011] The above-mentioned short-process method for preparing carbon-coated ruthenium fibers with a large aspect ratio is characterized in that the alkali metal and / or alkaline earth metal inorganic salt in step one is a eutectic salt of one or two of LiCl, NaCl, KCl, CsCl, CaCl2, MgCl2, and BaCl2; and the total addition amount of the alkali metal and / or alkaline earth metal inorganic salt accounts for 85% to 94% of the mixed salt material in terms of mass fraction.

[0012] The above-mentioned short-process method for preparing large aspect ratio carbon-coated ruthenium fibers is characterized in that the material of the non-carbon anode in step 2 is a NiFe2O4-based, TiB2-based, SnO2 or RuO2*TiO2 inert electrode; the material of the conductive cathode is stainless steel, nickel or titanium.

[0013] The RuO2*TiO2 inert electrode in the present invention refers to a composite electrode of RuO2 and TiO2.

[0014] The above-mentioned short-process method for preparing carbon-coated ruthenium fibers with a large aspect ratio is characterized in that the heating temperature in step 2 is 600°C to 900°C.

[0015] The above-mentioned short-process method for preparing carbon-coated ruthenium fibers with a large aspect ratio is characterized in that the voltage during the electrolysis in step 2 is 2.0V to 3.0V, and the electrolysis time is not less than 5h.

[0016] The above-mentioned short-process method for preparing large aspect ratio carbon-coated ruthenium fibers is characterized in that the diameter of the large aspect ratio carbon-coated ruthenium fibers in step three is 60nm to 100nm, and the aspect ratio is 100 to 300.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] 1. The present invention directly converts inorganic ruthenium salts and carbon salts into dissolved ruthenium and carbon electroactive ions in molten salt. Through reasonable proportioning, the electroactive ions ruthenium and carbon in the liquid molten salt are discharged and reduced at the cathode and assembled in situ to form carbon-coated ruthenium fibers with a large aspect ratio. The preparation process is short, the equipment requirements are low, the process is environmentally friendly and there is no emission of harmful wastes, which meets the strategic needs of developing green manufacturing.

[0019] 2. The present invention adopts non-carbon materials as the anode electrode for electrolysis, avoiding the use of conventional electrolytic graphite anodes, and effectively slowing down the emission of carbon-containing gas from the anode electrode in the traditional electrolysis process.

[0020] 3. The present invention realizes directional control of the micromorphology of carbon-coated ruthenium fiber by simply adjusting electrolysis parameters, such as electrolytic cell pressure, liquid molten salt target temperature, electrolysis time, etc., which is flexible, convenient and easy to implement.

[0021] 4. The process of the present invention is easy and convenient to continuously add ruthenium-containing, carbon inorganic salt raw material powders. At the same time, by rotating the cathode electrode, etc., it is easy to achieve batch preparation of large aspect ratio carbon-coated ruthenium fibers, and has good development prospects in continuous industrial preparation.

[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the process of preparing large aspect ratio carbon-coated ruthenium fibers by the short process of the present invention.

[0024] Figure 2 This is a physical picture of the conductive cathode after electrolysis in Example 1 of the present invention.

[0025] Figure 3 TEM image (a) of the high aspect ratio carbon-coated ruthenium fiber obtained in Example 1 of the present invention and an enlarged image of the coated structure (b).

[0026] Figure 4 This is the EDS component diffraction pattern of the high aspect ratio carbon-coated ruthenium fiber obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] Figure 1 The schematic diagram of the process of preparing carbon-coated ruthenium fibers with large aspect ratio by short process of the present invention is as follows: Figure 1 It can be seen that the present invention uses inorganic ruthenium salt and carbon-containing salt as ruthenium source and carbon source, mixes them evenly with alkali metal and / or alkaline earth metal inorganic salt, performs inorganic salt batching, obtains mixed salt material, heats the mixed salt material in a crucible in an inert atmosphere in a vertical tubular resistance furnace to form a stable liquid molten salt, and then lowers a two-electrode system consisting of a non-carbon anode and a conductive cathode below the liquid molten salt surface for electrolysis. After the electrolysis is completed, the non-carbon anode and the conductive cathode are lifted off the liquid molten salt surface, and after the furnace temperature drops to room temperature, the product on the conductive cathode is peeled off, and post-processed by repeatedly washing with deionized water and dilute hydrochloric acid to directly obtain large aspect ratio carbon-coated ruthenium fibers.

[0028] Example 1

[0029] This embodiment includes the following steps:

[0030] Step 1: Take 1.6g of RuCl3*nH2O and 8g of CaCO3 as ruthenium source and carbon source, mix them evenly with 150.4g of CaCl2, and then put them into a drying oven and dry them for 15h to prepare 160g of mixed salt;

[0031] Step 2: Continuously introduce Ar gas into the vertical tube resistance furnace, then heat the mixed salt material obtained in step 1 to 900°C in the crucible of the vertical tube resistance furnace and keep it warm to form a stable liquid molten salt, then lower the two-electrode system consisting of the non-carbon anode SnO2 and the conductive cathode nickel sheet below the liquid molten salt surface, set the voltage between the cathode and the anode to 2.5V, and carry out continuous electrolysis for 6 hours;

[0032] Step 3. After the electrolysis in step 2 is completed, the non-carbon anode SnO2 and the conductive cathode nickel sheet are lifted off the surface of the liquid molten salt. After the furnace temperature drops to room temperature, the introduction of Ar gas is stopped, and the product on the conductive cathode nickel sheet is peeled off. After repeated washing with deionized water and dilute hydrochloric acid, the high aspect ratio carbon-coated ruthenium fiber is directly obtained.

[0033] Figure 2 is a physical picture of the conductive cathode after electrolysis in this embodiment, Figure 2 It can be seen that this embodiment uses the method of molten salt electroreduction of ruthenium and carbon-containing electroactive ions to achieve effective deposition of ruthenium and carbon on the cathode electrode.

[0034] Figure 3 TEM image (a) of the carbon-coated ruthenium fiber with a large aspect ratio obtained in Example 1 and an enlarged image of the coated structure (b), Figure 3 It can be seen that the cathode product obtained in this embodiment forms an obvious coated fiber morphology and exhibits the characteristics of a large aspect ratio fiber, indicating that the parameter conditions of this embodiment successfully obtained a large aspect ratio carbon-coated ruthenium fiber.

[0035] Figure 4 The EDS component diffraction pattern of the carbon-coated ruthenium fiber with a large aspect ratio obtained in this embodiment is shown in FIG. Figure 4 It can be seen that the large aspect ratio carbon-coated ruthenium fiber obtained in this embodiment is mainly composed of ruthenium and carbon elements; there is also a small amount of oxygen element, which may be some defective oxygen-containing functional groups in the fiber.

[0036] After testing, the diameter of the large aspect ratio carbon-coated ruthenium fiber prepared in this embodiment is 60nm-100nm, and the aspect ratio is 100-300.

[0037] In this embodiment, the inorganic ruthenium salt can also be one of RuCl3, K2RuCl6, Na2RuCl5*nH2O, and RuO2, the carbon-containing salt can also be one of Na2CO3, Li2CO3, K2CO3, MgCO3, and BaCO3, and the alkali metal or / and alkaline earth metal inorganic salt can also be a eutectic salt of one or two of LiCl, NaCl, KCl, CsCl, CaCl2, MgCl2, and BaCl2.

[0038] The material of the non-carbon anode in this embodiment can also be NiFe2O4-based, TiB2-based, RuO2*TiO2 inert electrode, and the material of the conductive cathode can also be stainless steel or titanium.

[0039] Example 2

[0040] This embodiment includes the following steps:

[0041] Step 1: Take 9.0g of Na2RuCl5*nH2O and 18.0g of Li2CO3 as ruthenium source and carbon source, mix them evenly with 153.0g of eutectic salt of NaCl and CaCl2 (the molar ratio of CaCl2 to NaCl is 0.53:0.47), and then put them into a drying oven for drying for 24h to prepare 180g of mixed salt;

[0042] Step 2: Continuously introduce Ar gas into the vertical tube resistance furnace, then heat the mixed salt material obtained in step 1 to 850°C in the crucible of the vertical tube resistance furnace and keep it warm to form a stable liquid molten salt, then lower the two-electrode system consisting of the non-carbon anode TiB2 and the stainless steel conductive cathode to below the liquid molten salt surface, set the voltage between the cathode and the anode to 2.0V, and carry out continuous electrolysis for 8 hours;

[0043] Step 3. After the electrolysis in step 2 is completed, the non-carbon anode TiB2 and the stainless steel conductive cathode are lifted off the surface of the liquid molten salt. After the furnace temperature drops to room temperature, the introduction of Ar gas is stopped, and the product on the stainless steel conductive cathode is peeled off. After repeated washing with deionized water and dilute hydrochloric acid, the large aspect ratio carbon-coated ruthenium fiber is directly obtained.

[0044] After testing, the diameter of the large aspect ratio carbon-coated ruthenium fiber prepared in this embodiment is 60nm-100nm, and the aspect ratio is 100-300.

[0045] In this embodiment, the inorganic ruthenium salt can also be one of RuCl3, RuCl3*nH2O, K2RuCl6, and RuO2, the carbon-containing salt can also be one of Na2CO3, K2CO3, CaCO3, MgCO3, and BaCO3, and the alkali metal or / and alkaline earth metal inorganic salt can also be a eutectic salt of one or two of LiCl, NaCl, KCl, CsCl, CaCl2, MgCl2, and BaCl2.

[0046] The material of the non-carbon anode in this embodiment can also be NiFe2O4-based, SnO2, RuO2*TiO2 inert electrodes, and the material of the conductive cathode can also be nickel or titanium.

[0047] Example 3

[0048] This embodiment includes the following steps:

[0049] Step 1: Take 4.5g of RuO2 and 12.0g of Li2CO3 as ruthenium source and carbon source, mix them evenly with 133.5g of eutectic salt of NaCl and LiCl (the molar ratio of LiCl to NaCl is 0.72:0.28), and then put them into a drying oven for drying for 24h to prepare 150.0g of mixed salt material;

[0050] Step 2: Continuously introduce Ar gas into the vertical tube resistance furnace, then heat the mixed salt material obtained in step 1 to 600°C in the crucible of the vertical tube resistance furnace and keep it warm to form a stable liquid molten salt, then lower the two-electrode system consisting of the non-carbon anode RuO2*TiO2 and the titanium sheet conductive cathode to below the liquid molten salt surface, set the voltage between the cathode and the anode to 3.0V, and carry out continuous electrolysis for 5 hours;

[0051] Step 3. After the electrolysis in step 2 is completed, the non-carbon anode RuO2*TiO2 and the titanium sheet conductive cathode are lifted off the surface of the liquid molten salt. After the furnace temperature drops to room temperature, the introduction of Ar gas is stopped, and the product on the titanium sheet conductive cathode is peeled off. After repeated washing with deionized water and dilute hydrochloric acid, the high aspect ratio carbon-coated ruthenium fiber is directly obtained.

[0052] After testing, the diameter of the large aspect ratio carbon-coated ruthenium fiber prepared in this embodiment is 60nm-100nm, and the aspect ratio is 100-300.

[0053] In this embodiment, the inorganic ruthenium salt can also be one of RuCl3, RuCl3*nH2O, K2RuCl6, Na2RuCl5*nH2O, the carbon-containing salt can also be one of Na2CO3, K2CO3, CaCO3, MgCO3, BaCO3, and the alkali metal or / and alkaline earth metal inorganic salt can also be a eutectic salt of one or two of LiCl, NaCl, KCl, CsCl, CaCl2, MgCl2, BaCl2.

[0054] The material of the non-carbon anode in this embodiment can also be NiFe2O4-based, TiB2-based, SnO2-based inert electrode, and the material of the conductive cathode can also be stainless steel or nickel.

[0055] Example 4

[0056] This embodiment includes the following steps:

[0057] Step 1: Take 4.0g of K2RuCl6 and 16.0g of Li2CO3 as ruthenium source and carbon source, mix them evenly with 180.0g of eutectic salt of NaCl and KCl (the molar ratio of KCl to NaCl is 1:1), and then put them into a drying oven for 18h to prepare 200g of mixed salt material;

[0058] Step 2: Continuously introduce Ar gas into the vertical tube resistance furnace, then heat the mixed salt material obtained in step 1 to 750°C in the crucible of the vertical tube resistance furnace and keep it warm to form a stable liquid molten salt, then lower the two-electrode system consisting of the non-carbon anode TiB2 and the stainless steel conductive cathode to below the liquid molten salt surface, set the voltage between the cathode and the anode to 2.8V, and carry out continuous electrolysis for 6 hours;

[0059] Step 3. After the electrolysis in step 2 is completed, the non-carbon anode TiB2 and the stainless steel conductive cathode are lifted off the surface of the liquid molten salt. After the furnace temperature drops to room temperature, the introduction of Ar gas is stopped, and the product on the stainless steel conductive cathode is peeled off. After repeated washing with deionized water and dilute hydrochloric acid, the large aspect ratio carbon-coated ruthenium fiber is directly obtained.

[0060] After testing, the diameter of the large aspect ratio carbon-coated ruthenium fiber prepared in this embodiment is 60nm-100nm, and the aspect ratio is 100-300.

[0061] In this embodiment, the inorganic ruthenium salt can also be one of RuCl3, RuCl3*nH2O, Na2RuCl5*nH2O, and RuO2. The carbon-containing salt can also be one of Na2CO3, K2CO3, CaCO3, MgCO3, and BaCO3. The alkali metal or / and alkaline earth metal inorganic salt can also be a eutectic salt of one or two of LiCl, NaCl, KCl, CsCl, CaCl2, MgCl2, and BaCl2.

[0062] The material of the non-carbon anode in this embodiment can also be NiFe2O4-based, SnO2, RuO2*TiO2 inert electrodes, and the material of the conductive cathode can also be stainless steel or nickel.

[0063] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing carbon-coated ruthenium fibers with a large aspect ratio by a short process, characterized in that: The method comprises the following steps: Step 1: Mixing an inorganic ruthenium salt and a carbon-containing salt as a ruthenium source and a carbon source with an alkali metal or / and an alkaline earth metal inorganic salt, and then drying the mixture in a drying oven for not less than 12 hours to obtain a mixed salt material; Step 2: heating the mixed salt material obtained in step 1 in a crucible in an inert atmosphere in a vertical tubular resistance furnace to form a stable liquid molten salt, and then lowering a two-electrode system consisting of a non-carbon anode and a conductive cathode below the liquid molten salt surface for electrolysis; Step 3. After the electrolysis in step 2 is completed, the non-carbon anode and the conductive cathode are lifted off the surface of the liquid molten salt. After the furnace temperature drops to room temperature, the product on the conductive cathode is peeled off, and the large aspect ratio carbon-coated ruthenium fiber is directly obtained after repeated washing with deionized water and dilute hydrochloric acid.

2. The method for preparing carbon-coated ruthenium fibers with a large aspect ratio by a short process according to claim 1, characterized in that: The inorganic ruthenium salt described in step 1 is one of RuCl3, RuCl3*nH2O, K2RuCl6, Na2RuCl5*nH2O, and RuO2; in terms of mass fraction, the added amount of the inorganic ruthenium salt is 1.0% to 5.0% of the mixed salt material.

3. The method for preparing carbon-coated ruthenium fibers with a short process according to claim 1, characterized in that: The carbon-containing salt in step 1 is one of Na2CO3, Li2CO3, K2CO3, CaCO3, MgCO3, and BaCO3; in terms of mass fraction, the amount of the carbon-containing salt added is 5% to 10% of the mixed salt material.

4. The method for preparing carbon-coated ruthenium fibers with a large aspect ratio by a short process according to claim 1, characterized in that: The alkali metal and / or alkaline earth metal inorganic salt in step 1 is a eutectic salt of one or two of LiCl, NaCl, KCl, CsCl, CaCl2, MgCl2, and BaCl2; in terms of mass fraction, the total amount of the alkali metal and / or alkaline earth metal inorganic salt added accounts for 85% to 94% of the mixed salt material.

5. The method for preparing carbon-coated ruthenium fibers with a large aspect ratio by a short process according to claim 1, characterized in that: The material of the non-carbon anode in step 2 is NiFe2O4-based, TiB2-based, SnO2 or RuO2*TiO2 inert electrode; the material of the conductive cathode is stainless steel, nickel or titanium.

6. The method for preparing carbon-coated ruthenium fibers with a short process according to claim 1, characterized in that: The heating temperature in step 2 is 600°C to 900°C.

7. The method for preparing carbon-coated ruthenium fibers with a short process according to claim 1, characterized in that: The voltage during electrolysis in step 2 is 2.0V to 3.0V, and the electrolysis time is not less than 5h.

8. The method for preparing carbon-coated ruthenium fibers with a short process according to claim 1, characterized in that: The diameter of the large aspect ratio carbon-coated ruthenium fiber in step 3 is 60nm-100nm, and the aspect ratio is 100-300.

Citation Information

Patent Citations

  • Ruthenium / carbon nanotube flexible positive electrode material and preparation method and application thereof

    CN113725444A